TRENDS FORMING LOGISTICS SERVICES MARKET AS AN INDICATOR FOR BUSINESS DEVELOPMENT - Prokhorova, Viktoriya (Social Economics, 2018)
In the article the tendencies forming market logistic services are considered as an indicator development enterprise. Essence complex logistic and stages origin logistic are considered. Analysed determination concept "logistic" and authorial determination this concept essence that consists in the process optimal distribution material, informative and financial streams is given, by planning, organization, management and control, with the purpose cost and satisfaction necessities consumers cutout. Reasons origin logistic are certain. Principles construction the logistic system and logistic channels distribution are considered. The mechanism forming administrative decision offers an author on introduction functional logistic management.